2022
DOI: 10.3390/electronics11071044
|View full text |Cite
|
Sign up to set email alerts
|

SAGMAD—A Signature Agnostic Malware Detection System Based on Binary Visualisation and Fuzzy Sets

Abstract: Image conversion of byte-level data, or binary visualisation, is a relevant approach to security applications interested in malicious activity detection. However, in practice, binary visualisation has always been seen to have great limitations when dealing with large volumes of data, and would be a reluctant candidate as the core building block of an intrusion detection system (IDS). This is due to the requirements of computational time when processing the flow of byte data into image format. Machine intellige… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Real-time detection, particularly in streaming environments, is becoming imperative to swiftly identify and counteract malware propagation. As the volume of malware samples and feature spaces continues to expand, scalability concerns must be addressed [44,[86][87][88][89][90][91][92][93][94][95][96][97][98].…”
Section: Open Challengesmentioning
confidence: 99%
“…Real-time detection, particularly in streaming environments, is becoming imperative to swiftly identify and counteract malware propagation. As the volume of malware samples and feature spaces continues to expand, scalability concerns must be addressed [44,[86][87][88][89][90][91][92][93][94][95][96][97][98].…”
Section: Open Challengesmentioning
confidence: 99%
“…Deveci et al, [10] showed the Delphi method for interval type-2 fuzzy evidence. Saridou et al, [11] industrialized the recognition systems created on fuzzy logic. Many decision-makers have used the theory of FS in a choice of contexts, such as artificial networks, game theory, pattern recognition, and medicine.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, two feature selection strategies, static and dynamic, are proposed for the best possible malware classification in the used dataset. Using fuzzy logic [27,28] in conjunction with metaheuristic optimization, a twostage feature selection strategy is proposed for selecting dynamic features. To detect and categorize An-droid malware applications, a hybrid model based on fuzzy optimization mixed with meta-heuristic optimization methods, hybrid of enhanced MFO [29] and MVO [30] is evaluated as wrappers.…”
Section: Introductionmentioning
confidence: 99%